S216. CASE REPORT OF TREATMENT OF NEUROLEPTIC MALIGNANT SYNDROME IN CHILD ADOLESCENT. (18th May 2020) - Doo Kim, Moon; Nam, Beomwoo; Shim, Se-Hoon; Lim, Eun-Sung; Park, Sung-Yong; Lee, Sang-Yeol; Bahk, Won-Myong
Abstract: Background: Neuroleptic Malignant Syndrome is a rare clinical syndrome occurring due to idiosyncratic reaction after use of neuroleptics. We report a case of neuroleptic malignant syndrome in an adolescent patient with schizophrenia after treatment with antipsychotics. Methods: Case report. Results: A 15-year-old male Schizophrenic patient was admitted to the psychiatric closed ward due to worsening of psychotic symptoms on July of 2017. Pineal cystoma and pituitary microadenoma were detected incidentally on MRI, and consultation with the department of pediatrics recommended close observation. After treatment with 6mg of risperidone in combination with 300 mg of quetiapine, psychotic symptoms improved enough to be discharged. Since March 25th of 2019, due to manifestation of paralytic ileus from worsening of underlying constipation, all the oral medications were stopped along with NPO for treatment; in addition, IM injection of haloperidol was only allowed for the symptom control. The day before the onset of neuroleptic malignant syndrome, IM injection of 15 mg of haloperidol and 10 mg of lorazepam resulted in vomiting, headache, fever of 39℃, systemic tremor and stiffness, confusion in consciousness, tachycardia and sweating. On April 1st of 2019, with suspicion of neuroleptic malignant syndrome, the patient was transferred to ICU at our institution. Blood work-up performed on day of admission at ICU indicated CPK 2836 IU/L and myoglobulin 337.2 ng/ml, and CPK, after peaking at 4493 IU/L, continuously decreased and was normalized by the 18th day at ICU. Diazepam (IV), dantrolene, domperidone, L-Dopa/benserazideand and cold blanket were applied because the patient continuously screamed due to fever, stiffness, tremor, and psychotic symptoms. Even though confusion improved after 3 days, nausea and vomiting persisted for 8 days. Tremor, stiffness, and fever were stabilized after 3 days. Tachycardia improved after 17 days. Recovery of hematologic abnormalities such as increased CPK and myoglobulin and leukocytosis were followed by stabilization of tremor, stiffness, and high fever on the 18th day. The patient was transferred out of ICU after 18 days, and symptoms were all stabilized after treatment with clozapine. Discussion: Evaluation of risk factors of NMS in patients requiring neuroleptics is most critical in order for prompt differentials and early intervention. Known risk factors are 1) male, 2) combination of more than two antipsychotic, 3) history of previous EPS symptoms or NMS, 4) psychiatric disorders such as severe agitation, mood disorder, or delirium, 5) recent initiation or increasing dose of antipsychotics, 6) IM injection of antipsychotics, 7) poor physical conditions like dehydration, infection, malnutrition, brain tumor, encephalitis, or AIDS, 8) use of zuclopenthixol acetat (clopixol acuphase), and 9) substance abuse. In this case, because the patient had 6 of the risk factors described above, which are biological vulnerabilities due to pineal cystoma and pituitary micro adenoma, dehydration and malnutrition caused by paralytic ileus, and sudden change in IM antipsychotics and dosage, it was critical to consider more carefully in medication injection and changes in dosage. Once diagnosed with NMS, immediate hydration and efforts to lower body temperature are critical to prevent complications like acute renal failure, and use of dantrolene, bromocriptine, and benzodiazepine is helpful in shortening the treatment period. In cases of NMS in patients who cannot terminate use of neuroleptics due to underlying mental disorders, ECT is an effective method to treat both NMS and mental disorders. Safety and efficacy of ECT have been already proven, and it is highly recommended when needed.